The Effect Of Accounting Higher Education And Understanding Of Business And Professional Ethics On Emotional Intelligence Students Department Of Accounting (Studies At Institute Of Business (Iob), Universidade Dili (Undil) And Universidade Da Paz (Unpaz) - Joasenita Hornay; Sutrisno T; Zaki Baridwan; Roekhudin Roekhudin (ABM: International Journal of Administration, Business and Management, 2022)
The purpose of this study was to examine and analyze the level of accounting high education and understanding of business and professional ethics affect the emotional intelligence of students majoring in Accounting IOB, UNDIL and UNPAZ. Research design can be interpreted as a structured work plan in terms of the relationships between variables comprehensively in such a way that the research results can provide answers to research questions. The plan includes the things that the researcher will do, from making hypotheses and their operational implications to the final analysis (Umar, 2007; 6). The sample is part of the number and characteristics possessed by the population. If the population is large and it is impossible for researchers to study everything in the population, for example due to limited funds, finances, time, and energy and so on, the researcher can use the sample (Umar, 2007, 78). The sampling technique used is the saturated sample technique, as many as 103 students. Majoring in accounting at three universities, IOB 36 students, UNDIL 33 students, and UNPAZ 34 students. The results of this study indicate that accounting higher education has a negative and significant effect on the emotional intelligence of accounting students and understanding of business and professional ethics has a positive and significant effect on the emotional intelligence of accounting students at IOB, UNDIL and UNPAZ.